Assessing NODM Patients for Early PDAC Diagnosis: Incidence of NODM Before PDAC Diagnosis and Subsequent PDAC Risk - Satish Munigala; Benjamin Bowe; Divya S. Subramaniam; Hong Xian; Arna N. Gowda; Sunil G. Sheth; Rajiv Chhabra; Thomas E. Burroughs; Banke Agarwal (Cancer Medicine, 2025)
ABSTRACT Background New‐Onset Diabetes Mellitus (NODM) is often an early manifestation of pancreatic cancer (Pancreatic Ductal Adenocarcinoma, PDAC). However, there is limited information about (1) the duration prior to PDAC diagnosis when the annual incidence of NODM starts significantly exceeding that in age‐matched controls, (2) the percentage of PDAC patients diagnosed with NODM in the years preceding, and (3) the risk of PDAC following NODM in time when the PDAC risk is significantly higher than in controls. Methods Using the nationwide VA database, we evaluated the annual incidence of NODM for 15 years preceding the PDAC diagnosis and in the age‐ and sex‐matched controls (1:5 matching). In the second part, we evaluated the long‐term risk and predictors of PDAC in NODM patients and controls. Results The case–control study comprised 8198 PDAC patients and 40,992 matched controls. The higher annual incidence of NODM in PDAC patients was statistically significant up to 15 years before PDAC diagnosis. 69.2% of PDAC patients had NODM in the preceding 15 years versus 38.0% of controls. PDAC risk in the 15 years following NODM was 0.60% compared to 0.13% in the controls (aHR 3.83, 95% CI 3.68–3.98, p < 0.001). The risk of PDAC is more pronounced in the 1 year following NODM (aHR 9.07, 95% CI 8.33–9.87) than the subsequent 5 years (aHR 2.98, 95% CI 2.82–3.15). Conclusion NODM pre‐dates PDAC diagnosis in most patients with PDAC. Further evaluation of NODM patients for PDAC has the potential to become a feasible strategy for diagnosing more early‐stage resectable PDACs.